PROBLEMATIKA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DAN UPAYA MENGATASINYA - Hamdanah; Nuryati (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2022)
The aim of the research is to explore the problems of SKI teachers and efforts to activate student learning as ideal role models, both in personal and social life. As for efforts to increase student achievement cannot be separated from the various factors that influence it. In this case, a creative teacher is needed who can make learning more interesting. This research uses a quantitative approach with a descriptive approach, which is located at Madrasah Aliyah Nurul 'Amal Pusat Menes Pandeglang, Banten. Data collection techniques in research, namely interviews, document observation are used in data collection in order to obtain the required data in accordance with the research focus. The results of the discussion in the research are the problems of SKI learning experienced by students from the large amount of material and the way teachers teach them by using conventional methods and still not using technology in learning. In addition, the support of school principals in overcoming the problems of SKI learning is by providing supervision related to the use of learning methods, learning media and finding learning resources both physically and digitally.